(untitled) (CIPEEX, 2025)
Introduction: Gestational diabetes mellitus (GDM) is one of the most prevalent obstetric complications, increasing the risk of type 2 diabetes for both mother and child. Adequate diet and regular physical activity contribute to glycemic control and reduce complications. Objective: To review the literature to see if interventions involving physical activity and a healthy diet can reduce blood glucose levels in women with GDM. Methods: This is a literature review conducted based on the PICO strategy. Studies published in the last five years, in Portuguese or English, that specifically addressed pregnant women diagnosed with gestational diabetes who underwent interventions involving physical activity and diet were included. The search, conducted in August 2025, was conducted in the PubMed and BVS databases, using the descriptors "gestational diabetes," "physical activity," and "diet," combined with the Boolean operator AND. A total of 85 articles were identified, of which only four met the eligibility criteria. Results: The four included studies showed that the combination of a controlled diet and regular physical activity improves glycemic control in pregnant women with gestational diabetes. Some studies reported reduced fasting and postprandial blood glucose levels, reduced need for medication, a lower prevalence of gestational hypertension and preeclampsia, and a reduction in fetal macrosomia. Conclusion: The evidence analyzed confirms that interventions combining a controlled diet and regular physical activity are safe and effective strategies for managing gestational diabetes mellitus, contributing to reducing the need for pharmacological treatment and the occurrence of maternal and neonatal complications.